Toll-like receptor agonists as cancer vaccine adjuvants - Donghwan Jeon; Ethan Hill; Douglas G. McNeel (Human Vaccines & Immunotherapeutics)
Cancer immunotherapy has emerged as a promising strategy to treat cancer patients. Among the wide range of immunological approaches, cancer vaccines have been investigated to activate and expand tumor-reactive T cells. However, most cancer vaccines have not shown significant clinical benefit as monotherapies. This is likely due to the antigen targets of vaccines, “self” proteins to which there is tolerance, as well as to the immunosuppressive tumor microenvironment. To help circumvent immune tolerance and generate effective immune responses, adjuvants for cancer vaccines are necessary. One representative adjuvant family is Toll-Like receptor (TLR) agonists, synthetic molecules that stimulate TLRs. TLRs are the largest family of pattern recognition receptors (PRRs) that serve as the sensors of pathogens or cellular damage. They recognize conserved foreign molecules from pathogens or internal molecules from cellular damage and propel innate immune responses. When used with vaccines, activation of TLRs signals an innate damage response that can facilitate the development of a strong adaptive immune response against the target antigen. The ability of TLR agonists to modulate innate immune responses has positioned them to serve as adjuvants for vaccines targeting infectious diseases and cancers. This review provides a summary of various TLRs, including their expression patterns, their functions in the immune system, as well as their ligands and synthetic molecules developed as TLR agonists. In addition, it presents a comprehensive overview of recent strategies employing different TLR agonists as adjuvants in cancer vaccine development, both in pre-clinical models and ongoing clinical trials.